Public Expenditures in Agriculture in Mozambique: What Investments are Required for Technical Change, and What Drives Investment Decisions? - Mogues, Tewodaj; Benin, Samuel; Woldeyohannes, Sileshi (International Food Policy Research Institute, 2013)
This paper undertakes a two-pronged investigation of agricultural public investments in Mozambique. Firstly, it estimates the public resources required in the agricultural sector—both in magnitude and in type or composition—in order for the country to sustainably meet its own development goals as established in the context of the CAADP framework. Secondly, by situating the existing literature within a conceptual framework, it explores what are the driving factors behind the amount of public funds allocated to and for agriculture and the differential attention that different types of public investments receive in resource allocation decision making.